Identification of molecular markers linked to woolly apple aphid (Eriosoma lanigerum) (Hausmann) resistance in apple - Christians, Gillian Eleanore (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2003.